Innovation of Using Hybrid Modules in Muhammadiyah Elementary School in Sleman as Alternative Distance Learning Solutions in the Covid-19 Pandemic - Abdullah Mukti; Agus Suroyo; Hasanudin (Al-Misbah (Jurnal Islamic Studies), 2022)
The pandemic has turned the education and learning process into distance learning and learning from home. These changes do not necessarily run smoothly. However, there are many obstacles and problems. These include internet network access, the absence of quotas and the process of changing without being conditioned before. Not to mention the complaints from parents who usually leave it entirely to the school, but with the pandemic, parents seem to be "forced" to be involved in the distance learning process. One of the innovations developed by the Muhammadiyah School in Sleman at the elementary and junior high school levels is using a hybrid module. This research is a descriptive qualitative research on the application and effectiveness of the hybrid module among students of SD Muhammadiyah SMP in Sleman Regency. The number of respondents who were given a questionnaire on the implementation and effectiveness of the module was selected to represent all sub-districts in Sleman Regency, totalling 17 sub-districts. So that the number of research targets consists of 34 principals, students, and parents of students from all Muhammadiyah elementary schools throughout Sleman Regency, totalling 98 respondents. The results of the study reveal the innovation of the Hybrida module at Muhammadiyah Middle School in Sleman as an alternative to Distance Learning solutions during the Covid-19 pandemic in Sleman Regency. All 15,407 Muhammadiyah elementary school students and 9,063 Muhammadiyah junior high school students use the module as a learning resource for teachers, students and parents and guardians of students. The effectiveness of the innovation of using Hybrid Modules at Muhammadiyah Middle School in Sleman as an Alternative to Distance Learning Solutions During the Covid-19 Pandemic, there were many benefits. The benefits of hybrid modules are also discussed in this article.